Power, Sexism, and Gender: Factors in Biblical Interpretation - Orme, Laura M. Northrop (Journal of psychology and theology, 2017)
This study assesses individual social attitudes and ideological beliefs regarding systems of power and sexism (i.e., Authoritarianism, Conservatism, Traditionalism, Social Dominance Orientation [SDO], Hostile Sexism [HS], and Benevolent Sexism [BS]) in relationship to Bible interpretation choice about passages related to gender. Data were collected from 216 conservative Protestant Christian churchgoers. It was hypothesized that individuals with higher levels of Authoritarianism, Conservatism, Traditionalism, SDO, HS, and BS would prefer interpretations that endorse gender hierarchy. The results supported these hypotheses, finding Traditionalism and HS to be the primary factors related to interpretation choice. Additionally, it was hypothesized that any significant difference between men and women regarding interpretation choice would be explained by individual differences in these social attitudes and ideological beliefs. Men were significantly more likely than women to prefer Bible interpretations oriented toward gender hierarchy, and this difference was primarily explained by Traditionalism and HS.